وثيقة حقوق الإنسان للأمم المتحدة : دراسة تخليلية في ضوء القرآن الكريم - مهدي، فخريزال (al-Jami'ah al-Islamiyah al-'Alamiyah bi-Maliziya, 2013)
This research attempts to introduce human rights from the Qur'anic perspective and to compare it with the articles of Universal Declaration of Human Rights. It highlights the challenges that United Nations face in implementing decisions related to human rights. The research demonstrates the similarities and differences in human rights decided by the United Nations and the human rights from the holy Qur'an including the difficulties in practicing human rights that United Nations call for. At the beginning, the research discusses the definitions of “human” and “rights” from the Qur'anic and Sunnah as well as legal (law) perspectives, then moves to the issuance of the document of the United Nations for Human Rights and clarifies the status of a human and his rights in the Qur'an. The researcher highlights the protection of humans based on the Qur'an and its characteristics in Islam, focusing and refuting some of the suspicions raised by the enemies of Islam in the area of human rights such as women's rights and freedom of worship. It is worth mentioning that the researcher has adopted several methods such as descriptive, analytical and comparative. The researcher concludes that Islamic religion is the first law which protects human rights both in this world and the hereafter because its rules and regulations cover all areas of life. However, what the United Nations is propagating and calling in its decision on human rights issues (Universal Declaration of Human Rights) since 1948 is only an echo of what the religion of Islam has brought to the followers, and what is in contrast to Islam, is often contrary to human nature.